Analisis Bibliometrik: Penerapan Mobile Application “Bank Sampah” sebagai Layanan Pengelolaan Sampah di Era Digital - Hs, Arifatul Azzarah; Sunusi, Putri Melinda; Nurwahyuni, Andi; Reskita, Dewiyanti; D, Nurjannah; Mustari, Muhammad Laits Meilano; Sonni, Alem Febri (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2025)
This study examines the trends in research on the implementation of mobile waste bank applications for waste management in the digital era in Indonesia from 2019 to 2023. A bibliometric analysis was conducted using VOSviewer to identify keyword co-occurrence and the clustering of related topics. The findings reveal that research on mobile waste bank applications has seen a significant increase in publications, with a peak of 120 articles in 2022. However, a decline in publications was observed in 2023, with only 80 articles published. The most cited article in this field,